Edukasi Dan Pengenalan Dini Terjadinya Stunting Pada Balita Di Desa Tanrara Kabupaten Gowa - Mikawati, Mikawati; Suriyani, Suriyani; M, Muaningsih; Pratiwi, Resky; Lusiana, Evi (PT.Mantaya Idea Batara, 2023)
Stunting is a condition where growth and development is chronically stunted and caused by direct and indirect factors, it is very important for parents to know about stunting. The purpose of this activity is that parents are expected to be able to recognize stunting and carry out early prevention stimulation for toddlers. The method used is the distribution of educational leaflets, the provision of health education and discussion of questions and answers to mothers who bring toddlers at the village hall of Tanrara Kec. Bontonompo, Gowa Regency. The results obtained from this activity were that the enthusiasm of parents in participating in this activity was very high, marked by the liveliness of answering the questions given and participating in the activity until it was finished.